Challenging cause of bullous eruption of the hands in the Arctic. (8th November 2018) - Kristiansen, Bo; Penninga, Luit; Diernaes, Jon Erik Fraes
Abstract : Phytophotodermatitis is caused by deposition of photosensitising compounds on the skin followed by ultraviolet exposure. We present an unusual case of a 29-year-old Australian male visiting Greenland who presented with severe itchy bullous eruption on his hands. The cause was a combination of exposure to lime fruit juice and prolonged sun exposure from the Arctic midnight sun.